STUDY OF UNDERWATER FRICTION STIR WELDING PROCESS PARAMETERS ON AA6005-T6 MATERIAL FOR MARINE INDUSTRY AND UNDERWATER STRUCTURE APPLICATIONS - Mulyadi, Mulyadi; Fahruddin, A'rasy; Firdaus, Rachmat; Ahfas, Akhmad (Jurnal Rekayasa Mesin, 2025)
This research explores Underwater Friction Stir Welding (UFSW) on AA6005-T6 material, focusing on identifying optimal process parameters to enhance joint quality in terms of macrostructure, tensile strength, impact strength, and hardness. The results from UFSW welding of AA6005-T6 indicate that optimal process parameters yield better joint quality. The macrostructure of specimens with optimal parameters, such as spc 7, demonstrates improved homogeneity and minimal defects. The highest tensile strength and impact strength were achieved in this specimen, with a tensile strength of 117.7 MPa and an impact strength of 0.944 joule/mm², compared to other specimens. Meanwhile, the hardness of the welded joints, which is lower than the base metal, reflects the influence of process parameters on the microstructure of the joints. Overall, these results underscore the importance of precise parameter control to achieve high-quality welds. This research provides valuable insights into the effectiveness of process parameters in producing high-quality joints in underwater welding environments and highlights the potential of UFSW as an innovative method for underwater welding.